Trends of Religious Moderation Through Islamic Religious Education in Indonesian Universities: Systematic Literature Review - Afwadzi, Benny (Proceeding of International Conference on Islamic Education (ICIED), 2025)
Radicalism was a crucial problem in higher education institutions in Indonesia. To resolve this problem, the Ministry of Religious Affairs of the Republic of Indonesia introduced the terminology of religious moderation in 2019. This ministry also provided instructions for integrating religious moderation into universities’ Islamic Religious Education (IRE). After, many studies emerged to examine its effectiveness in reducing radicalism. To synthesize and provide a comprehensive thematic analysis of previous studies, this research examined religious moderation in IRE in Indonesian universities using a systematic literature review method. This research discovered 20 primary literature related to the theme. This research found that the values of religious moderation tend to be tolerance or tasamuh and non-violence. Researchers' strategies and methods to develop religious moderation are varied, such as internalization, ISRA-based IRE, social learning models, and discussions. Meanwhile, the impact of cultivating religious moderation in IRE was able to shape students’ moderate thoughts and attitudes while minimizing radicalism. This research proposed the role of religious moderation in IRE as a means of overcoming radicalism, intolerance, and religious violence in Indonesia. Besides, it allowed educators to articulate strategies and methods according to their capacities. Furthermore, IRE learning based on religious moderation in Indonesia became the best practice for other countries facing problems of radicalism, extremism, and terrorism.